Global trends and future projections of migraine burden in children aged 5 to 14 from 1990 to 2050 - Liao, Shuzhen; Qian, Guifeng; Huang, Huaqing; Fu, Haishou (Frontiers in Neurology, 2025)
Migraine is a leading cause of disability, yet its burden in children aged 5 to 14 remains underexplored. Using Global Burden of Disease (GBD) 2021 data, we analyzed global, regional, and national migraine burdens from 1990 to 2021. Age-standardized incidence (ASIR), age-standardized prevalence (ASPR), and disability-adjusted life years (DALY) were assessed, with estimated annual percent change (EAPC) used for trend evaluation. A Bayesian Age-Period-Cohort (BAPC) model projected incidence to 2050. Globally, migraine cases rose by 39.5% (21.95 to 26.87 million), though ASIR, ASPR, and DALY rates remained stable. Low-middle Sociodemographic Index (SDI) regions had the highest prevalence (31.19 million) and DALY (1.11 million), while high SDI regions recorded the highest female incidence rates. Western Sub-Saharan Africa showed the largest increases across all metrics (EAPCs > 3.0). Brazil reported high ASIR and DALY, while Thailand had the greatest DALY reduction, likely due to effective public health measures. Projections suggest declining ASIR, ASPR, and DALY rates by 2050. These findings indicated absolute cases of migraine have increased due to population growth, the age-standardized burden has remained stable over time. Strengthened surveillance, targeted screening in low-middle SDI regions, and school-based awareness programs in high-burden countries are essential to mitigating migraine-related disability in this vulnerable population.